In Vitro Evaluation of Antidiabetic and Anti-Inflammatory Activities of Five Selected Syzygium Leaves Ethanolic Extract as Alpha-Glucosidase Inhibitors and Anti-denaturation of Bovine Serum Albumin (BSA) - Meiliza Ekayanti; Feri Setiadi; Siti Aminah; Alam Almaaz Afandi (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Diabetes mellitus (DM) has become a major health problem worldwide, with a continuous increase in mortality due to complications caused by hyperglycemia. Chronic hyperglycemia is often associated with inflammation due to increased production of free radicals. Objective: This study’s main objective is to assess antidiabetic and anti-inflammatory properties in vitro of five particular Syzygium leaves extract (S. cumini, S.aqueum, S. malaccense, S. polyanthum, and S. aromaticum) using alpha-glucosidase and Bovine Serum Albumin (BSA).  Methods: The five of selected Szygium leaves were macerated by using ethanol 96%, each extract was assessed in vitro for antidiabetic activity by analyzing the inhibitory of alpha-glucosidase using acarbose as strandard, and anti-inflammatory activity by analyzing the inhibitory denaturation of BSA Heat-induced and BSA induced by 2,2-diphenyl-1-picrylhydrazine (DPPH) with Sodium diclofenac as standard. Results: The IC50 of α-glucosidase inhibition was 76.235 µg/mL (strong) for S. malaccense and 0.241 µg/mL (very strong) for the acarbose standard. The greater IC50 of antidenaturation of BSA with heat-induced was S. polyanthum (95.7 µg/mL) and sodium diclofenac standard (59.25 µg/mL) both were strong inhibitor. Along with greater anti-denaturation of BSA, DPPH-induced S. malaccense (90.320 µg/mL) and sodium diclofenac standard (43.301 µg/mL), both of which are strong inhibitors. Conclusion: The ethanol extract of Syzygium leaves has the potential to be developed as an antidiabetic and anti-inflammatory herbal medicine, particularly S. malaccense and S. polyanthum leaf extracts, which provided greater activity in this study.